Unusual cardiac manifestation of hypereosinophilic syndrome. Issue 922 (1st August 2002) - Subhash, H S; Asishkumar, M; Jonathan, M
Abstract : Hypereosinophilic syndrome was diagnosed in a 14 year old girl who presented with recurrent syncope. An ambulatory electrocardiogram revealed intermittent type 2 second degree left atrioventricular (AV) block. Focal thinning of the interventricular septum was noted on echocardiography, contrary to the commoner finding of regional ventricular wall thickening among patients with hypereosinophilic syndrome. High grade AV block as a manifestation of hypereosinophilic syndrome is rare and focal thinning of the left ventricle as a manifestation of the syndrome has not been described earlier.